Visualization of the relationship between metabolism and lung diseases from the perspective of bibliometric analysis: research trends and future prospects - Wang, Ming-Yan; Mo, Xing-Yu; Yi, Meng-Xu; Lu, Hong-Yan (Frontiers in Medicine, 2024)
Background: Extensive research has examined the role of metabolism in lung disease development, yet a comprehensive literature review remains absent despite numerous publications. Objective: This study aims to visualize and assess the advancements in research on metabolism and its role in lung diseases. Methods: Publications from January 1, 1991, to April 30, 2024, related to lung diseases and metabolism were sourced from the Web of Science Core Collection and analyzed using CiteSpace 6.2.R4, VOSviewer 1.6.19, Bibliometrix, R Studio, and various online tools. Results: A total of 1,542 studies were collected and processed through these platforms for literature analysis and data visualization. The analysis revealed a sharp increase in annual publications on metabolism and lung diseases, with the United States and China emerging as leading contributors. Current research trends highlight a shift toward investigating metabolic reprogramming of immune cells in the context of lung diseases. Moreover, genes such as TNF, DIF, AKT1, INS, IL-6, CXCL8, IL-1β, TP53, NF-κB1, MTOR, IFNG, TGF-β1, HIF1α, VEGFA, IL-10, NFE2L2, PPARG, AKT, CRP, STAT3, and CD4 have received significant attention in this research domain. Employing a bibliometric approach, this study offers a comprehensive and objective examination of the knowledge landscape, shedding light on the evolving trends in this field. The findings serve as a valuable resource for researchers, offering a clearer perspective on the advancements in metabolism-related lung disease studies.